The impact of a sibling's life‐limiting genetic condition on adult brothers and sisters. Issue 7 (27th April 2017) - Brown, Erica; Coad, Jane; Franklin, Anita
Abstract : It is estimated that rare diseases affect the lives of over three million people in the United Kingdom. Of these, a significant proportion are children and young people with genetic life‐limiting or life‐shortening conditions. This study used a qualitative approach with in‐depth semi‐structured interviews to explore the experiences of 10 adult siblings of a baby diagnosed with Trisomy 13 (Patau syndrome) or Trisomy 18 (Edward syndrome). Findings illustrate that parental grief from the time of their child's diagnosis onward is also experienced by siblings. Although young adults may have conflicting feelings as a bereaved sibling, there is evidence that the experience impacts on their world views and their attitudes about prospective and expectant parenthood. The study highlights the importance of providing siblings with short‐term and long‐term support from the time of their brother's or their sister's diagnosis onward and provides new understanding about benefit of professional and peer support in helping young adults develop resilience and coping strategies.